Are Party Activists Potential Opinion Leaders? - Vergani, Matteo (Javnost-The Public, 2011)
The article investigates whether or not party activists are potential opinion leaders, presenting the results of field research on four local branches of the Italian PD (Democratic Party). First, the article examines the most relevant “opinion leaders” theories, proposing an original method for recognising potential opinion leaders: the identification of three main features of the ideal-type of opinion leader (the identification with the group, the technical expertise, the social capital) within the biographies of the social actors. Second, the article presents a case-study assessing whether party activists of the local PD branches possess these qualities or not, by analysing the data coming from qualitative fieldwork: ethnographic sessions within the four local branches, and forty biographical interviews with the party activists. At the end of the article some remarks will be given about the methodology used, about the idea of a party opinion leadership and about the role of party activists in changing the voters’ mind.